ANALYSIS OF DELAYS PREVENTION EFFORTS IN THE LOADING PROCESS AT XIN LIN HAI MV 16 - Marupah PIP (JURNAL VENUS, 2026)
This research aims to understand and prevent delays in the loading process and preparation of the loading space. The subject of the study is the process of preparing the loading room in the MV. Xin Lin Hai 16. The method used in writing this scientific paper is qualitative descriptive, by means of observations, interviews, and literature studies related to delays in the loading process due to lack of supervision from mualim I, bosun, and helmsman. The results of the study showed that problems in the loading room cleaning process were caused by a lack of communication, coordination, and maintenance of the loading room cleaning equipment in accordance with procedures to prevent delays in the loading process. The conclusion of this study is to improve supervision, coordination, and communication between ship crew and workers, as well as to perform routine maintenance on cargo room cleaning equipment.